Antimicrobial casein/poly(vinyl alcohol) electrospun nanofibers-based dressings - Nobre, D. (2025)
Diabetes affects millions globally, with a rising prevalence. Chronic wounds are one of its major complications, due to the healing difficulty, highlighting the need for innovative solutions to improve the treatments efficacy. Electrospun nanofiber dressings show promising due to their ECM-like structure, oxygen permeability, and potential for bioactive functionalization. In this study, casein/poly(vinyl alcohol) (CAS/PVA) nanofibers were electrospun with antimicrobial compounds: Octiset®, polyhexanide, and ZnO particles. After crosslinking with glutaraldehyde (GA), the nanofibers mats were characterized regarding their morphology, swelling capacity, enzymatic degradation, drug release behavior, cytotoxicity, hemocompatibility, irritability potential and antimicrobial potential. They demonstrated notable swelling capacity, and therefore potential to absorb exudate and maintain a moist healing environment in the wound. Those containing polyhexanide and Octiset® (CAS/PVA_Poli and CAS/PVA_Octi) showed a significant drug release for over 4–8 h, that prolonged at a slower rate for 24 h, being mainly diffusion-controlled. The crosslinker reduced the amount of drug released and the degradation of the nanofibers but increased their water absorption capacity. CAS/PVA_Poli and CAS/PVA_Octi exhibited the most interesting set of results, as besides being non-cytotoxicity, hemocompatible and non-irritant, presented excellent antimicrobial efficacy and superior performance when compared with the crosslinked samples. They were effective against Staphylococcus aureus, Escherichia coli, and Candida albicans, and in particular against Methicillin Resistant Staphylococcus aureus and Streptococcus pyogenes which are a dangerous threat in diabetic wounds. Overall, their morphological similarity with the extracellular matrix and excellent biological properties, turns them good candidates to be used in dressings for the treatment of diabetic wounds.